Developing a library accessibility plan a practical guide for librarians - Marrall, Rebecca M., 1983- (Practical guides for librarians, 2020)
"This book provides experienced and detailed research-based guidance for library professionals charged with creating a comprehensive accessibility plan for their organization. This practical guide is designed to help librarians understand the challenging issues often inherent in the different types of accessibility barriers"--